2017
DOI: 10.1007/s00436-017-5503-1
|View full text |Cite
|
Sign up to set email alerts
|

New data on Neodiplostomum americanum Chandler and Rausch, 1947 (Digenea: Diplostomidae), in the Great Horned Owl Bubo virginianus Gmelin, 1788 and the Eastern Screech Owl Megascops asio Linnaeus, 1758 in Mississippi, USA

Abstract: Neodiplostomum americanum Chandler and Rausch, 1947 has been reported from six species of owls in North America. At present, there are no molecular data for this species and gene sequence data from Neodiplostomum Railliet, 1919 are limited. A freshly deceased specimen of the Great Horned Owl Bubo virginianus Gmelin, 1788 and a freshly deceased specimen of the Eastern Screech Owl Megascops asio Linnaeus, 1758 were collected in Oktibbeha County, Mississippi in 2014 and 2016, respectively. Neodiplostomum american… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Furthermore, our specimens and the material of Woodyard et al . (2017) conform to the original morphological description of N. americanum by Chandler and Rausch (1947). Our morphological examination of voucher specimens of adult N. americanum sequenced by Blasco-Costa and Locke (2017) revealed that the taxon was misidentified.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Furthermore, our specimens and the material of Woodyard et al . (2017) conform to the original morphological description of N. americanum by Chandler and Rausch (1947). Our morphological examination of voucher specimens of adult N. americanum sequenced by Blasco-Costa and Locke (2017) revealed that the taxon was misidentified.…”
Section: Discussionsupporting
confidence: 75%
“…Our specimens of N. americanum are conspecific with specimens previously published by Woodyard et al . (2017) based on partial sequences of 28S, the ITS region and cox 1. Furthermore, our specimens and the material of Woodyard et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species of the genus Neodiplostomum Railliet, 1919 infects both mammals and birds (HONG & SHOOP, 1994). Nevertheless, some parasite species within the genus appear to be specific to a certain group of hosts; for instance, Richardson & Kinsella (2010) ; WOODYARD et al, 2017), N. reflexum (CHANDLER & RAUSCH, 1947;GALLAS & SILVEIRA, 2013), and N. delicatum (KINSELLA et al, 2001). The poor condition of these two collected specimens makes species identification impossible.…”
Section: Trematodamentioning
confidence: 99%